O efeito da massagem terapêutica nos sintomas climatéricos em mulheres pós-menopausadas com insônia: um estudo clínico randomizado - Oliveira, Denise de Souza [UNIFESP] (2011)
In the climacteric period, approximately 80% of women are affected by consequences of hypoestrogenism: physiological and psychological alterations, hot flashes, nycturia, mood alterations. These changes contribute to the increase of insomnia prevalence in this phase, which affects approximately 28% to 63% of postmenopausal women. The presence of such symptoms associated with socio-cultural conditions, such as retirement, appreciation of youth, aging, reflect directly on quality of life of this population. As hormone therapy is indicated in certain cases and is not indicated for some patients, there has been an increase in the demand for complementary or alternative therapies, including therapeutic massage, which may relieve insomnia symptoms in the climacteric period. The present study is presented in two studies. The first one, a pilot study with seven individuals, evaluated the effects of therapeutic massage on post-menopausal insomniac women and demonstrated subjective and objective sleep improvement. The results of this study led us to conduct a second one, now a randomized and controlled trial, including 44 women, distributed into 3 groups (control, passive movement and therapeutic massage). The results of the questionnaires demonstrated improvement in sleep, climacteric symptoms and quality of life.